Bimbingan Agama Islam Sebagai Penguat Kesadaran Bagi Resident Di Yayasan Rehabilitasi Narkoba Mutiara Abadi Binjai - Agung Gumelar; Agus Suriadi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Drug problems have a fairly broad scope and are always related to various aspects such as medical aspects and mental health aspects. By using drugs, a person's personality is damaged in the family structure, social and religious environment. It can be seen from the age group, in drug use which until now has penetrated all circles, whether it is an early age, teenagers or adults. In general, drug addicts are far from being religious, so they do not even know which one to do. what is bad and what is good, what is useful and which is harmful. As for most of them, they only know God and their religion, but do not do what is commanded in their religion, so they fall into the valley of drugs. From the results of research conducted, most of the residents really are far from understanding religion. Thus, the existence of religious guidance for residents can fortify and equip themselves to live a more focused life with the religious guidance, such as the lecture method and the Koran. Religious guidance can be carried out properly and run as expected if the residents have great initiates in themselves to seek religious knowledge. In the application of this guidance, it is carried out according to the circumstances and conditions of the resident. As residents hope that the services provided can change themselves for the better and in accordance with the lives of people in general.